Review of the genus Tachytes Panzer (Hymenoptera: Crabronidae: Crabroninae) of South Korea, with description of one new species - Back, Yeong-Bin; Kim, Jeong-Kyu (Zootaxa, 2014)
Korean species of the genus Tachytes Panzer are reviewed. Four previously known species are confirmed, and one new species, Tachytes gyusanus is described. The new species is very similar to T. modestus, but it differs critically in the form of male genitalic capsule. A revised key to South Korean species, a description of the new species, and digital images and line drawings of diagnostic characteristics are provided.